2012
DOI: 10.1007/s12282-012-0362-1
|View full text |Cite
|
Sign up to set email alerts
|

Malignant granular cell tumor of the breast: case report and literature review

Abstract: Granular cell tumors (GCTs) are uncommon soft tissue tumors that mostly occur in patients between 40 and 60 years of age and can occur at various body sites. Malignant granular cell tumors (MGCTs) comprise less than 2 % of GCTs and are mostly found on the lower extremities, especially the thighs. These tumors grow more rapidly than benign GCTs, and most importantly, they can metastasize. We describe an MGCT that presented as a right breast mass in a 79-year-old Japanese woman. Local excision was performed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 23 publications
0
29
0
3
Order By: Relevance
“…In contrast to clinical findings, mammography, ultrasonography and MRI positron emission tomography (PET) with 2-[fluorine-18] fluoro-2-deoxy-d-glucose (FDG) can correctly differentiate GCT from a malignant tumor (11). Fine-needle aspiration cytology and frozen section methods are inadequate for definitive diagnosis of GCT (12). The large core-needle biopsy did accurately predict a GCT in our patient.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast to clinical findings, mammography, ultrasonography and MRI positron emission tomography (PET) with 2-[fluorine-18] fluoro-2-deoxy-d-glucose (FDG) can correctly differentiate GCT from a malignant tumor (11). Fine-needle aspiration cytology and frozen section methods are inadequate for definitive diagnosis of GCT (12). The large core-needle biopsy did accurately predict a GCT in our patient.…”
Section: Discussionmentioning
confidence: 58%
“…Malignant forms of GCTs are very rare (1-3% of all GCT cases). Chen et al (6) and Akahane et al (12) described malignant GCTs in breast. Criteria for malignancy are not consistent; adjacent tissue and/or vascular invasion, high mitotic activity, and size >4-5 cm were discussed, but only the presence of metastases was accepted as explicit criterion (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…In our case it was difficult to definitively distinguish metastatic tumours from multi‐centric/synchronous “benign” tumours. Both tumours had low FDG uptake on PET scan where some studies have shown that malignant GCTs are usually intensely FDG avid . On imaging, the caecal lesion was larger than the pulmonary lesions and was calcified, the latter often a sign of chronicity.…”
Section: Discussionmentioning
confidence: 95%
“…Jardines L, et al [7] reported soft tissue GCT with uncertain malignant potential histologically but had regional nodal metastasis radiologically. Akahane K, et al [8] reported an atypical GCT of the breast with clinical features of malignancy. This report concluded that high level Ki-67 alone was considered as a proof of malignancy.…”
Section: Discussionmentioning
confidence: 99%